2017
DOI: 10.5935/1415-2762.20170040
|View full text |Cite
|
Sign up to set email alerts
|

Strategies Used by Nurses in the Functional Readjustment of Nursing Workers

Abstract: RESUMOObjetivo: conhecer as estratégias de enfermeiros ao receber o trabalhador de enfermagem em readaptação funcional. Metodologia: estudo qualitativo, descritivo exploratório, realizado em um hospital universitário no Sul do Brasil. Os dados foram coletados por meio de entrevista semiestruturada com 19 enfermeiros, entre maio e julho de 2016. Para análise e interpretação dos dados, optou-se pela proposta operativa de Minayo. Resultados: as informações convergiram para duas categorias: acolhimento e cuidado c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…As for the lack of participation of workers in important decisions in the process of functional readaptation, a study shows that the conducts that take place in an imposing way have a negative impact for workers in this condition 10 . At the same time, they impact on the management and organization of work, considering that in the units, the nurse needs to manage the care including these workers, so that the restrictions presented by them are preserved 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the lack of participation of workers in important decisions in the process of functional readaptation, a study shows that the conducts that take place in an imposing way have a negative impact for workers in this condition 10 . At the same time, they impact on the management and organization of work, considering that in the units, the nurse needs to manage the care including these workers, so that the restrictions presented by them are preserved 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Institutional charges and the lack of monitoring and follow-up on the part of the institution, the follow-up carried out by the immediate supervisor and the lack of care in the institution were perceived as negative by the participants. An investigation carried out with nurses who received workers undergoing functional readaptation at their units showed that the work organization process needs to be rethought, so that it can stimulate appreciation, respect and sensitivity towards professionals who return to work, considering limits and potentials 16 . About this, it is mentioned that in addition to physical access conditions, it is urgent to rethink humanization in the work context for workers 10 .…”
Section: /14mentioning
confidence: 99%